The Influence of Involvement in Behaviour Problems on Learners’ Academic Performance in Nairobi County, Kenya - Ong’era, Lynett Kemunto (IJRDO- Journal of Educational Research, 2016)
This study sought to determine the influence of involvement in behaviour problemson learners’ academic performance in Nairobi County, Kenya. There is abundant evidence tosupport the correlation between children’s behaviour problems and academic performance.Behaviour problems are exhibited by learners of different ages and educational levels andinterfere with learning, development and also negatively affect those around the learner’senvironment. They may include aggression, drug and substance abuse and teenage sex,among others. These behaviour problems significantly affect learners’ academic performanceand hence academic achievement. Further, behavioural problems interrupt academicprogress and create conditions that make it difficult to achieve educational objectives.Findings of this study revealed that overall academic performance of learners who wereinvolved in behaviour problems was significantly lower than those who were not involved inbehaviour problems.